2007
DOI: 10.2340/16501977-0102
|View full text |Cite
|
Sign up to set email alerts
|

Multi-disciplinary rehabilitation after hip fracture is associated with improved outcome: A systematic review

Abstract: Background: while hip fractures are an important cause of disability, dependency and death in older adults, the benefit of multi-disciplinary rehabilitation for people who have sustained hip fracture has not been demonstrated. Methods: Systematic review of randomized controlled trials which compare co-ordinated multi-disciplinary rehabilitation with usual orthopaedic care in older people who had sustained a hip fracture. Outcome measures included: mortality, return home, "poor outcome", total length of hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 20 publications
1
77
0
3
Order By: Relevance
“…Despite these reports, however, there exists a consensus that effective rehabilitation with respect to mobility and function for people who have sustained hip fractures, whether or not they also have dementia, is crucial to their return to their previous dwelling places in the community. [16][17][18][19][20][21][22] Several strategies have been suggested for health care professionals to reduce the negative impact of cognitive and behavioural symptoms, thereby improving prognoses for these patients. 23,24 However, not all health care professionals are aware of strategies for working with patients with dementia or put these strategies into practice.…”
mentioning
confidence: 99%
“…Despite these reports, however, there exists a consensus that effective rehabilitation with respect to mobility and function for people who have sustained hip fractures, whether or not they also have dementia, is crucial to their return to their previous dwelling places in the community. [16][17][18][19][20][21][22] Several strategies have been suggested for health care professionals to reduce the negative impact of cognitive and behavioural symptoms, thereby improving prognoses for these patients. 23,24 However, not all health care professionals are aware of strategies for working with patients with dementia or put these strategies into practice.…”
mentioning
confidence: 99%
“…Knowledge syntheses summary-There were 13 secondary/knowledge synthesis (CPG or SR) studies identified related to the examination of some aspect of exercise prescription (therapeutic exercise, physical activity, active rehabilitation) in an older adult fracture population [74][75][76][77][78][79][80][81][82][83][84][85][86]. Table 4 provides a summary of the purpose, population(s) included and the key 'exercise prescription' related practice and/or research findings or recommendations in each synthesis, including a footer note for citation details of any subsequent updated or new of knowledge syntheses published after the final July 3, 2009.…”
Section: Data Sorting and Chartingmentioning
confidence: 99%
“…One study had a mixed fracture focus, including any fracture in older adults [74], whereas, the remaining 12 studies specifically focused on one type of fracture, including eight hip fracture [75][76][77][78][79][80][81][82], two ankle fracture [83,84], one proximal humerus fracture [85] and one distal radius fracture study [86]. There was no knowledge synthesis study found for vertebral fracture populations.…”
Section: Data Sorting and Chartingmentioning
confidence: 99%
See 1 more Smart Citation
“…From a systematic review, multi-disciplinary rehabilitation after hip fracture surgery is associated with improved outcomes [8] in which nursing roles or nursing care are not specifically stated. Gregersen et al [9] reported that multidisciplinary geriatric in-hospital intervention that included a nurse with geriatric expertise reduced LOS but did not affect patient outcome in terms of discharge destination, in-hospital mortality, or 3month mortality.…”
Section: Introductionmentioning
confidence: 99%